Burnout Among Nurses During the Covid-19 Pandemic - Henny Yulianita; Furkon Nurhakim; Anik Sulistiawati; Irman Somantri; Kosim Kosim; Kurniawan Yudianto; Firman Sugiharto (Malahayati Nursing Journal, 2023)
ABSTRACT Burnout is a global phenomenon. The prevalence of burnout among nurses in Indonesia is around 60%. During the COVID-19 pandemic, the number of patient visits to the Public health centre has increased. This study aims to describe burnout in nurses at the Public health centre during the COVID-19 pandemic. This study uses a quantitative descriptive with a cross-sectional approach. The population is 40 health centre nurses using a sampling technique that is the total population. This study used the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) as an instrument with final validity test values ranging from -0.701 to 0.966 and a reliability test of 0.83. Data analysis uses univariate analysis, which is shown in the form of a frequency distribution. Almost all respondents experienced moderate burnout, as many as 34 nurses (85%). Based on the burnout dimension show that the dimensions of emotional exhaustion are 27 nurses (67.5%), the dimension of depersonalization is 31 nurses (77.5%), and the dimension of achievement decline is 29 nurses (72.5%), mostly in the medium category. The high burnout of Public health centre nurses will affect the performance of nurses in providing nursing services to patients. The impact of the pandemic has also become a source of stress for nurses in providing services. The possibility of nurses coming into contact with asymptomatic COVID-19-infected patients is substantial. This becomes a burden for nurses in providing services. Keywords: Burnout, Covid-19, Health Centre, Nurse, Pandemic